PD-1 Inhibitor Maintenance Therapy Combined Iodine-125 Seed Implantation Successfully Salvage Recurrent Cervical Cancer after CCRT: A Case Report - Guangchao Wei; Fuxin Guo; Ang Qu; Weijuan Jiang; Yuliang Jiang; Junjie Wang; Ping Jiang (Current Oncology, 2021)
Cervical cancer is the fourth most common cancer in females worldwide. Patients with stage III and IV cervical cancer based on the Federation of Gynecology and Obstetrics (FIGO) classification have higher recurrence rates. Because of organs at risk (OAR) protection and the low indication rate of salvage surgery, the choice of treatment is always challenging. Systemic chemotherapy is palliative and can be performed in conjunction with surgery or radiotherapy; however, it has no significant benefit to survival. Brachytherapy and stereotactic body radiotherapy (SBRT) are characterized by extremely high radiation doses applied to tumor cells while sparing the normal tissues. Several studies have investigated the efficacy of these technologies in recurrent cervical cancer and showed promising results. The immune checkpoint inhibitors approach was also investigated and showed promising results too. Herein, we report a case of a patient with cervical cancer that recurred five months after adjuvant chemotherapy and concurrent chemoradiotherapy. The disease prognosis after interstitial implantation brachytherapy (IIB) was determined. Then, the patient underwent radioactive 125I-seed implantation combined with PD-1 inhibitor treatment. The patient exhibited a partial response after seed implantation, and up to now, the duration of this partial response was 24 months.